PERBEDAAN EFEKTIFITAS RETENSI DAN PREVENTIF KARIES BAHAN PIT DAN FISSURE SEALANT - Hesti Witasari Jos Erry; Agus Ardinansyah (ODONTO : Dental Journal, 2019)
Introduction: Dental caries is a fairly high dental disease that occurs in most countries, which is approximately 60-90% occur in children. Pit and Fissure sealants are materials that are placed on pits and dental fissures that aim to prevent dental caries. There are several types of materials which often used as pit and sealant fissures, including Glass Ionomer Cement (GIC) and Resin-based Sealant/Composite Resin (RK). The purpose of this study is analising the differences in the effectiveness of retention and prevention of caries in GIC and RK pit and fissure sealants in elementary school children. Method: The subjects are 76 permanent teeth of 7-8 years old children with a grouping of 38 teeth each based on the material tested of GIC and RK. Results: There is a significant differences between the pit and fissure sealant material of GIC and RK in the effectiveness of retention and prevention of caries. Conclusion: In the statistical calculation, the comparative effectiveness of retention and caries prevention pit and fissure sealant RK and GIC materials is significant difference. The RK material is more effective in retention and prevention of caries compared with GIC.